Development of Serial Technological Entrepreneurship as One of the Modern Trends of the World Economy: Challenges for Kazakhstan - Larissa P. STEBLYAKOVA; Evgeniy V. KRASNOV (Communications of International Proceedings, 2021)
The article focuses on a new trend in the development of the world economy - serial technological entrepreneurship, which involves the mass production of not only innovative products but also new technological businesses, as well as the widespread use of technological outsourcing. The authors analyzed the entrepreneurial activity of different countries, including the involvement of the adult population in high-tech entrepreneurship, determined the conditions for the transformation of entrepreneurship into a "conveyor" of innovative businesses. Using the example of the economy of Kazakhstan, the possibilities of integrating it into a new format of world economic development were investigated and recommendations were developed for activating innovation activities by forming an effective innovation system with an active role of the state in this process.
Keywords: Serial Technological Entrepreneurship; Innovation Policy; National Innovation System.